2011
DOI: 10.1002/cpp.680
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a trauma‐focused treatment approach for travel phobia

Abstract: Despite its prevalence and potential impact on functioning, there are surprisingly little data regarding the treatment responsiveness of travel phobia. The purpose of this non-randomized study was to evaluate the usefulness of a trauma-focused treatment approach for travel phobia, or milder travel anxiety arising as a result of a Road Traffic Accident (RTA). Trauma-focused Cognitive Behavioural Therapy (TF-CBT), and Eye Movement Desensitization and Reprocessing were used to treat a sample of 184 patients who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…Travel phobia was diagnosed in 57% of cases. Patients showed clinically significant decreases in symptoms, and the improvements were obtained within an average course of seven sessions of one hour each . The symptomologies of PTSD and travel phobia after RTCs have been found to overlap, implying that psychological interventions would benefit both conditions .…”
Section: Discussionmentioning
confidence: 97%
“…Travel phobia was diagnosed in 57% of cases. Patients showed clinically significant decreases in symptoms, and the improvements were obtained within an average course of seven sessions of one hour each . The symptomologies of PTSD and travel phobia after RTCs have been found to overlap, implying that psychological interventions would benefit both conditions .…”
Section: Discussionmentioning
confidence: 97%
“…To this end, EMDR is increasingly applied as a treatment for other (anxiety) disorders (De Jongh & Ten Broeke, 2009), such as driving phobias (De Jongh, Holmshaw, Carswell, & van Wijk, 2011), and other conditions and symptoms that developed following an adverse event (see for instance De Jongh & Ten Broeke, 2010;Maxfield & Melnyk, 2000). If the working memory model is a valid explanation for what occurs during EMDR, it would mean that taxing working memory is effective in resolving negative memories that play a role in, or underlie, a broad variety of psychological symptoms and conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Eye Movement Desensitization and Reprocessing (EMDR) represents an internationally well‐established and empirically validated treatment of PTSD . Some recent studies hinted on the beneficial effect of EMDR in patients with specific phobias . Indeed, one study, using a multiple baseline design, showed a significant reduction of self‐ and observer‐rated anxiety, dysfunctional beliefs concerning dental treatment, following two to three sessions of EMDR .…”
mentioning
confidence: 99%